2013
DOI: 10.1371/journal.pone.0056203
|View full text |Cite
|
Sign up to set email alerts
|

Transiently Transfected Purine Biosynthetic Enzymes Form Stress Bodies

Abstract: It has been hypothesized that components of enzymatic pathways might organize into intracellular assemblies to improve their catalytic efficiency or lead to coordinate regulation. Accordingly, de novo purine biosynthesis enzymes may form a purinosome in the absence of purines, and a punctate intracellular body has been identified as the purinosome. We investigated the mechanism by which human de novo purine biosynthetic enzymes might be organized into purinosomes, especially under differing cellular conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Follow-up studies have since suggested that the reported foci formation of transiently expressed human purine biosynthesis enzymes was independent of purines and thus may explain this discrepancy [22]. In order to more carefully assay for a potential purinosome, we additionally tested for the co-localization of yeast purine biosynthesis enzymes in foci.…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up studies have since suggested that the reported foci formation of transiently expressed human purine biosynthesis enzymes was independent of purines and thus may explain this discrepancy [22]. In order to more carefully assay for a potential purinosome, we additionally tested for the co-localization of yeast purine biosynthesis enzymes in foci.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, previous efforts using cells stably transfected with purinosome constructs did not yield visible purinosome bodies (Gooljarsingh et al 2001). Overexpression of proteins above their native levels has been shown to result in their aggregation (Cromwell et al 2006, Klein & Dhurjati 1995, Mayer & Buchner 2004, Yokota et al 2000, Zhang et al 2004), and the transiently overexpressed purine biosynthetic enzymes form intracellular bodies to extents that correspond to each enzyme’s predicted aggregation propensity (Zhao et al 2012). The resultant bodies are marked by ubiquitin and heat-shock chaperones, which suggests that they may represent aggregated protein clusters (Zhao et al 2012).…”
Section: Fibers and Focimentioning
confidence: 99%
“…For example, the six enzymes of the human de novo purine biosynthetic pathway were observed to reversibly form clusters, named purinosomes, in HeLa cells in response to purine availability 17,21 , though the role of expression levels and fluorescent fusions remains open 22 . Furthermore, in a recent study 18 of Saccharomyces cerevisiae it was observed that out of 800 GFP-tagged cytosolic proteins, 180 clearly displayed evidence of dynamic clustering, with many of these proteins involved in intermediary metabolism and stress response.…”
mentioning
confidence: 99%